The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1097/aud.0b013e31827ad9d3
|View full text |Cite
|
Sign up to set email alerts
|

Acoustic Stapedius Reflex Function in Man Revisited

Abstract: The stapedius reflex appears to offer some protection from the upward spread of masking of speech by background low-frequency noise at moderate levels, but not at high levels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 76 publications
0
4
0
Order By: Relevance
“…The airway transmission of the ear to which stimulus is given, cochlea, auditory nerve, cochlear nucleus, superior olivary complex and the facial nerve of the ear from which reflex will be obtained, nerve to stapedius, the stapes muscle and the middle ear must be normal for the formation of acoustic reflex (9,10). This path that the stimulus follows is known as the acoustic reflex arc.…”
Section: Discussionmentioning
confidence: 99%
“…The airway transmission of the ear to which stimulus is given, cochlea, auditory nerve, cochlear nucleus, superior olivary complex and the facial nerve of the ear from which reflex will be obtained, nerve to stapedius, the stapes muscle and the middle ear must be normal for the formation of acoustic reflex (9,10). This path that the stimulus follows is known as the acoustic reflex arc.…”
Section: Discussionmentioning
confidence: 99%
“…The amplitude of the stapedius reflex is decreased in patients with noiseinduced hearing abnormities even when their thresholds are normal at 1000 Hz, which confirms that their noisereduction system is affected [18]. A researcher showed that the stapedius reflex has an important function in decreasing internal sound in order to perceive external signals better [19]. This has a positive effect on language perception under noisy conditions.…”
Section: B) Function Of Middle Ear Skeletal Muscles In the Protectionmentioning
confidence: 57%
“…This acoustic reflex function explains why paralysis of the muscle causes hyperacusis (Rubini et al, 2020). The acoustic stapedius reflex is also reported to be involved in improved speech recognition at low‐frequency moderate noise levels (Aiken et al, 2013) as well as degraded speech recognition at high presentation levels (Shehorn et al, 2020). Further studies regarding the acoustic reflex feedback to the stapedius muscle are needed to confirm these theories.…”
Section: Discussionmentioning
confidence: 99%